RESPON PERTUMBUHAN DAN HASIL TANAMAN SAWI TERHADAP APLIKASI POC LIMBAH BUAH-BUAHAN PADA BEBERAPA KONSENTRASI - Lena Walunguru; Marsema Kaka Mone; Julian Abdullah (Politeknik Pertanian Negeri Kupang, 2018)
The research aiming knowing content macro and micro of organic fertilizer liquid from waste fruit papaya, apple, nanas, and kepok banana, and know influence granting organic fertilizer liquid to growth and results of mustard plants. The purpose of reseach through making organic fertilizer liquidwaste fruit papaya, apple, nanas, and kepok banana and experimend on the mustard plants are cultivation organically. Experimend of organic fertilizer liquid consist of eight treatment concentration that is 0, 5, 10, 15, 20, 25, 30, and 35 ml organic fertilizer liquid/l water. Research has been done on March until November 2018 in practice garden of the TIH program study and soil and water laboratory, IPB. The research used Completely Randomized Block Design. Research data were analyzed by analysis of variance (ANOVA), and test with Analysis of Variance and HonestlySignificant Difference (HSD) level 5% when there are differences. Observation parameters consist of supporting and main. The result of research that concentration 35 ml organic fertilizer liquid/l waterinfluential best to high plant namely 38,33 cm (not differ with concentration 30 ml organic fertilizer liquid/l water), the number of leaves most namely 14,42 (significant different with other concentration), the leaf area most namely 126,04 cm 2 (not differ with concentration 30 ml organicfertilizer liquid/l water), heaviest wet weight namely 200,95 g, and heaviest dry weight namely 15,29 g.